The Effects of Different Concentrations of Prunus serotina Extract on the Quality Characteristics of Raw and Cooked Pork Burger - Adrian Cristian ORĂDAN; Adrian Vasile TIMAR; Adriana Ramona MEMETE; Cristina Adriana ROSAN; Alin Cristian TEUSDEA; Simona Ioana VICAȘ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
Nowadays, there is a trend to enhance the properties of meat products by fortifying them with various plant-based extracts. The objective of the work was to fortify pork burgers with different concentrations of Prunus serotina extract (PSE) and to evaluate certain quality attributes (pH, cooking characteristics, color parameters, and sensory attributes) in both raw and cooked burgers. In addition, the content of total phenols and the antioxidant capacity were evaluated in burgers samples. The results revealed that the cooking characteristics were influenced by the addition of PSE in burgers. From the perspective of color parameters, the increase in the concentration of PSE results in a significant decrease (p<0.05) in the L* parameter, while the redness increases in raw burgers. In contrast, in the cooked burgers, these chromatic attributes exhibit an inverse relationship. Burgers with 10% PSE enriched showed a value of 2.04±0.01 µmol Trolox Equivalent (TE)/g and 0.49±0.001 mg galic acid equivalent (GAE) /g for antioxidant capacity and total phenols, respectively, even after cooking. The 2% PSE -fortified burgers, however, obtained the most appreciate after the sensory evaluation. In conclusion, our results have revealed that the extract of P. serotina can be used as a natural additive in the composition of pork meat burgers.